THE EFFECTIVENESS OF JIGSAW TECHNIQUE IN TEACHING WRITING DESCRIPTIVE TEXT - Moh Fauzi Bafadal (Muhammadiyah University of Mataram, 2015)
This study was about experimenting the effectiveness of Jigsaw technique in teaching writing descriptive text at second-grade students of SMPN 21 Mataram. The research method was quasi-experimental research with nonequivalent control group design. The finding showed the mean score of the experimental group was 13.3 and the mean score of the control group was 7.2. After analyzing the data, it was found that t-test was 3.657. The degree of freedom (df) was Nx+Ny-2 = 38 from 40 students as the samples. The researcher got score 2,042 for confident level 0.05 or 95% and score 2,750 for confident level 0.01 or 99%. It means that using the Jigsaw technique in teaching writing descriptive text is effective.